Translation and cross-cultural adaptation into Italian of the self-administered FLARE-RA questionnaire for rheumatoid arthritis - N. Ughi; T. Schioppo; I. Scotti; V. Merlino; A. Murgo; O. De Lucia; B. Fautrel; F. Guillemin; R. Christensen; F. Ingegnoli (Reumatismo, 2020)
The aim was to provide a translation into Italian with cross-cultural adaptation of the French FLARE-Rheumatoid Arthritis (RA) questionnaire, and to test its acceptability, feasibility, reliability and construct validity in a single-centre cohort study. The French version of the FLARE-RA questionnaire was cross-culturally adapted and translated into Italian following an established forward–backward translation procedure, with independent translations and backtranslations. To validate the Italian version we tested the internal validity with Cronbach’s alpha, test-retest reliability with the intraclass correlation coefficient, agreement between assessments with Bland-Altman plots and construct validity with Spearman’s correlation coefficients. The questionnaire was tested on 283 consecutive RA outpatients (mean age 56.1±13.9 years, 226/283 females, median disease duration 12.6 years ranging from 0.2 to 70.6). For the global score (11 items) the Cronbach’s alpha coefficient was 0.94. The intraclass correlation coefficient was 0.87 (95% CI, 0.76-0.96). The correlation of FLARE-RA global score was 0.59 (95% CI, 0.50-0.66) with the Disease Activity Score on 28 joints, 0.63 (95% CI, 0.55-0.71) with the Simplified Disease Activity Index, 0.77 (95% CI, 0.71-0.83) with the RA Impact of Disease and 0.67 (95% CI, 0.59-0.73) with the Health Assessment Questionnaire. The Italian version of the FLARE-RA is feasible, brief and easy to administer. The translated and cross-cultural adapted showed accordingly to be valid and reliable. This questionnaire has some practical advantages, such as clarity, comprehensiveness, simplicity, and a minimum filling time. The development of cross-cultural adapted questionnaires in different languages is of pivotal importance to obtain standardized and comparable data across countries.